(untitled) (Journal of Kidney Cancer, 2022)
An inflammatory myofibroblastic tumor (IMT) is a rare neoplasm with an unclear origin that can arise anywhere on the body. It contains spindle cells (myofibroblasts) with different inflammatory elements. Primary IMT of the kidney is a clinically rare disease and is difficult to differentiate from other renal malignancies. We reported a 49-year-old male who presented with right flank pain in the past year. A computed tomography scan showed a mixed density with slight heterogeneous enhancement mass in the upper pole of the right kidney, two small hypodense nodules invading the liver, and another mass in the lateral aspect of inferior vena cava. The patient underwent right radical nephrectomy and metastasectomy. IMT was confirmed by both postoperative histopathological examination and immunohistochemical assay. The patient recovered well after the operation, and no recurrence or metastasis was noted during the 12-month follow-up.